2008-2017 Bogota River Water Quality Assessment Based on the Water Quality Index (2019)
This article provides a deep analysis of the water quality at the upper basin of the Bogota River (Colombia) between 2008 and 2017. The Water Quality Index has been the indicator employed to determine the ecological status of the river.